2014
DOI: 10.1021/ie502711r
|View full text |Cite
|
Sign up to set email alerts
|

ReEngineered Feedstocks for Pulverized Coal Combustion Emissions Control

Abstract: New coal reaction technology called ReEngineered Feedstock (ReEF), consisting of post-recycled paper and plastics, was evaluated for combustion emissions control when cofiring with pulverized coal. Experiments were conducted with four types of ReEF in a 2 in. diameter laboratory-scale fluidized bed combustor system heated to 1200, 1400, and 1600°C. Flue gas emission was continuously monitored with an online infrared multigas analyzer and mass spectrometer. The results indicate that co-firing ReEF with coal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Wang et al [20] revealed the existence of a Na-based desulfurization product similar to burkeite e Na 6 (CO 3 ) (SO 4 ) 2 , which at high temperature can be formed through crystallization from molten phases of Na 2 CO 3 and Na 2 SO 4 (melting point (mp) 884 C [37]). This double salts was also identified by Zhu et al [15].…”
Section: Effect Of Reef™ Composition On Ash Behaviorsupporting
confidence: 77%
See 1 more Smart Citation
“…Wang et al [20] revealed the existence of a Na-based desulfurization product similar to burkeite e Na 6 (CO 3 ) (SO 4 ) 2 , which at high temperature can be formed through crystallization from molten phases of Na 2 CO 3 and Na 2 SO 4 (melting point (mp) 884 C [37]). This double salts was also identified by Zhu et al [15].…”
Section: Effect Of Reef™ Composition On Ash Behaviorsupporting
confidence: 77%
“…Regarding the Ca content, it is the highest in slag from cocombustion of ReEF™ with NaHCO 3 for a Na/Ca ratio of 0.1 followed by ReEF™ with a Na/Ca ratio of 0, suggesting the deposition on the probe of CaO and CaSO 4, which both have previously been identified in coal slag [7,15,34]. The sulfur content of the slag is the highest for the ReEF™ with Na/Ca ¼ 0, corroborating the hypothesis of the capture of CaSO 4 even though CaSO 4 itself has a relatively high melting temperature (1450 C) [20].…”
Section: Effect Of Reef™ Composition On Ash Behaviormentioning
confidence: 59%
“…As an example, concentration of SO 2 and NO 2 from coal combustors before gas cleaning is 200-2000 and 800 ppm, respectively. 30 In some countries, there are legislations to control concentration of emissions and to keep it below the standard levels. For example, according to the National Ambient Air Quality Standards (NAAQS) set by the Environmental Protection Agency (EPA) in the US, concentration of the released SO 2 and NO 2 must be below 100 and 75 ppb, respectively.…”
Section: In Situ Emissions Reduction In Coal Fired Boilersmentioning
confidence: 99%
“…Although statistics indicate that worldwide coal consumption has plateaued, its share of the total world energy consumption will remain substantial until 2040. , Coal currently supplies a third of all energy consumption worldwide and 40% of the world’s electricity needs . For many countries, coal will remain the major source of electricity for the foreseeable future . Coal combustion, however, has long been recognized as a principal source of air pollution due to the emission of criteria air pollutants, such as particulate matter, NO x , SO x , Hg, HCl, and trace elements resulting from the intrinsic fuel-bonded contaminants (e.g., heavy metals) and those generated during fuel combustion (e.g., dioxin, furans, and aromatics). , Therefore, great efforts have been devoted by governments and industries to develop more efficient and less polluting technologies, ensuring that coal will be a much cleaner source of energy in the decades to come…”
Section: Introductionmentioning
confidence: 99%